Reliability and validity of a Korean version of the children’s eating behavior questionnaire in anorexia context - Ko, Mi Mi; Lee, Sun Haeng; Chang, Gyu Tae; Lee, Boram (Frontiers in Nutrition, 2023)
Background: Although childhood anorexia is a common clinical disorder, there is no established tool for evaluating it. The Children's Eating Behavior Questionnaire (CEBQ) is a parent-reported measure designed to assess the eating behavior of children. We aimed to investigate the reliability and validity of the Korean version of the CEBQ (K-CEBQ) for children with anorexia.Methods: Parents of children with anorexia aged between 2 and 9 years participated in a survey conducted twice at 1-month intervals. The general characteristics and K-CEBQ scores of the children were recorded. To assess the reliability of the K-CEBQ, the internal consistency and testretest methods were used. Furthermore, correlation analysis was performed for each item and factor, and the discriminant validity was determined through comparison with the normal group. Optimal cut-off scores, which are based on the maximum area under the curve of the receiver operating characteristic curve, were calculated in two categories.Results: A total of 336 participants responded to the first survey, and the responses from 171 participants from the second survey were included in the analysis. The K-CEBQ showed relatively high internal consistency reliability (Cronbach's alpha = 0.738), and the retest demonstrated sufficient temporal stability. The relationship between each item of the K-CEBQ and the factor to which the item belongs showed a high correlation. There were significant differences between the anorexia and normal groups in two categories of the K-CEBQ: 'food approach' (p = 0.0063) and 'food avoidant' (p < 0.0001). The optimal cut-off values for the 'food approach' and 'food avoidant' category scores were 39.50 and 58.50 points, respectively.This study demonstrated that the K-CEBQ may be a reliable and valid tool for assessing the eating behavior of children with anorexia.